Adherence to planetary health diet index in relation to dietary diversity score and anthropometric indices among Iranian older adults - Maryam Karim Dehnavi; Razieh Tabaeifard; Hanieh Abbasi; Parisa Nezhad Hajian; Ahmadreza Dorosty Motlagh; Nick Bellissimo; Leila Azadbakht (BMC Public Health)
Abstract Background Ensuring a nutritious and sustainable diet for an expanding population presents a formidable challenge. In response to this pressing issue, the EAT-Lancet Commission has proposed a sustainable diet framework. This study aimed to investigate the relationship between Planetary Health Diet (PHDI), Dietary Diversity Score (DDS), and anthropometric indices among Iranian elders. Methods In this cross-sectional study, 398 participants aged ≥ 60 y were included. Dietary data was collected using a validated 168-item food frequency questionnaire and the DDS was computed based on five distinct food groups. Anthropometric measurements were conducted by standard protocol to derive relevant indices. Binary logistic and linear regression models, adjusted for potential confounders, were employed to analyze the association between adherence to PHDI and outcomes of interest using SPSS version 26. Result Subjects had a mean age of 63.28 years (SD = 3.58), ranging from 60 to 84 years, of whom 50% were females. PHDI was categorized into tertiles, with 34.7% of individuals in the highest tertile. Highest adherence to PHDI, compared to the lowest, was found to be inversely associated with a lower probability of high BMI (OR: 0.31, 95% CI: 0.17, 0.56), WC (OR: 0.53, 95% CI: 0.32, 0.90), and BRI (OR: 0.43, 95% CI: 0.25, 0.75) in fully adjusted models. Additionally, every 10-point increase in PHDI was linked to a 38%, 25%, and 28% decrease in odds of high BMI, WC, and BRI, respectively, after adjustments for potential confounders. Notably, no significant associations were observed between PHDI and other anthropometric indices or DDS in the fully adjusted model. Conclusion In conclusion, this study reveals a negative association between adherence to EAT-Lancet recommendations (PHDI) and unfavorable anthropometric measures in Iranian older adults. These findings suggest that promoting diets aligned with the EAT-Lancet guidelines may support healthier aging and help prevent obesity-related health risks. Further, prospective studies are needed to confirm these results and inform public health strategies.